1993
DOI: 10.1034/j.1600-0501.1993.040101.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligature‐induced peri‐implant infection in cynomolgus monkeys.Clinical and radiographic findings.

Abstract: The purpose of this study was to compare the effect of plaque accumulation in conjunction with or without placement of plaque-retaining ligatures on peri-implant and periodontal tissues. Four cynomolgus monkeys received 2 ITI (Type F) dental implants in edentulous areas of each side of the mandible. Following a healing period of 2 months with regular prophylaxis procedures twice per week, plaque was allowed to accumulate. After 1 month (day 0), silk ligatures were placed around 1 of the 2 implants. The third m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 0 publications
4
147
0
5
Order By: Relevance
“…Since the introduction of osseointegeration, many biomechanical and/or biological factors have been identified as sources of time-dependent marginal bone loss [11]. Essentially, biologically-driven marginal bone loss has been unquestionably well-demonstrated in animal studies [24,25,36]. The consequences of bacterial pathway regarding onset of peri-implant infections has been also explored [31].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of osseointegeration, many biomechanical and/or biological factors have been identified as sources of time-dependent marginal bone loss [11]. Essentially, biologically-driven marginal bone loss has been unquestionably well-demonstrated in animal studies [24,25,36]. The consequences of bacterial pathway regarding onset of peri-implant infections has been also explored [31].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of plaque and bleeding upon probing are associated with an increased risk of peri-implant diseases. 29,30 Experimental studies on peri-implantitis have shown that increased probing depth (PD) is related to bone loss and clinical attachment loss (CAL). 29,30 The prevalence of peri-implantitis in this study was 6.6% with PSIs and 15.6% with CIs.…”
Section: Psi P-value Healthymentioning
confidence: 99%
“…29,30 Experimental studies on peri-implantitis have shown that increased probing depth (PD) is related to bone loss and clinical attachment loss (CAL). 29,30 The prevalence of peri-implantitis in this study was 6.6% with PSIs and 15.6% with CIs. Although no differences in the prevalence of peri-implant diseases were found, there was one patient who had a ≥ 6mm pocket, in whom radiographically excess cement was found.…”
Section: Psi P-value Healthymentioning
confidence: 99%
“…Depending on the study, however, different references points were given [24,34,56,55,59]. This made comparative interpretation much more difficult [64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%